Community Economic Empowerment Through Coconut Shell Waste Management in Sungayang - Nofrianda, Muhamad; Irwandi, Irwandi; Susanti, Reni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This article describes community economic empowerment through the management of coconut shell waste in Nagari Sungai Patai, Sungayang District. The purpose of this study was to find out what empowerment strategies were carried out in the management of coconut shell waste in Nagari Sungai Patai, how the economic development of the community through coconut shell waste management and to determine the supporting and inhibiting factors in the treatment of coconut shell waste in Nagari Sungai Patai. The main problem in this thesis is the economic empowerment of the community through the management of coconut shell waste in improving the community's economy and reducing unemployment, changing people's views about waste from being just waste into a form of craft work that has economic value. The type of research used is field research with a qualitative approach. Data collection techniques used by researchers are observation, interviews and documentation. The data analysis technique used by the researcher is data reduction, and drawing conclusions. The guarantor of the validity of the data in this study uses triangulation of sources, techniques and time